BENEFITS OF USING GEOGRAPHY LEARNING MEDIA SMPN 16 IN PALANGKA RAYA - Silvia Arianti (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2017)
This study aims to find out about 1). availability of media conditions, 2). utilization of instructional media, 3). difficulties encountered and 4). efforts to benefit learning media geography SMPN 16 in Palangka Raya. This research is a descriptive research. Research data is quantitative data. The study was conducted at SMPN 16 in Palangka Raya. Population in this research is all teacher of SMPN geography in School and student of SMPN 16. Data collecting in this research is by using questionnaire method, interview and observation. The analysis technique used is descriptive statistical analysis. The results showed that 1). The availability of geography learning media at SMPN 16 includes: a). The types of media that most schools have are maps, atlases and globes b). Number of media including less category and c). The condition of learning media is quite good. 2). The benefits of learning media geography SMPN 16 in Palangka Raya can be seen from: media variations are moderate; The driving factor of selecting media is high; Students responses are high percent and student opportunities are moderate, 3). The difficulties faced by teachers are high. These difficulties include limited availability of media, personnel, cost, and time. 4) Efforts made teachers are moderate, Efforts by teachers include: teachers seek to organize media by asking through schools, selfemployed by making, searching, borrowing or buying themselves, assigning to students and donations.